Peran Guru PAI Dalam Meningkatkan Minat Baca Peserta Didik Melalui Kegiatan Wisata Qolbu di MTSN 3 Medan - Panggabean, Rizqi Fauzi Farhan; Matsum, Hasan; A, As’ad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study is entitled “The Role of PAI Teachers in Increasing Students’ Reading Interest through Qolbu Tourism Activities at MTsN 3 Medan”, there are chronic problems in reading books due to technological advances so that physical books have been abandoned especially for students at MTsN 3 Medan so that madrasah and teachers took the initiative to implement madrasah literacy called Qolbu tourism activities in an effort to increase students’ interest in reading at MTsN 3 Medan. This is the background for researchers to want to know the reading interest of students, the role of PAI teachers in increasing students’ interest in reading through Qolbu tourism activities, and what are the supporting and inhibiting factors for PAI teachers in Qolbu Tourism Activities at MTsN 3 Medan. The research method used is descriptive qualitative. Data collection techniques using observation, interview and documentation techniques. Data analysis is data reduction, data presentation and data conclusion. The results of the study revealed that students’ interest in reading in Qolbu tourism activities has changed a lot as evidenced by the level of the level that more and more students are interested and happy to read books. The role of PAI teachers in increasing students’ interest in reading in qolbu tourism activities is as a motivator, director, guide and evaluator. Then the supporters and obstacles of PAI teachers on Qolbu tourism activities at MTsN 3 Medan are caused by internal and external factors. Internal factors are caused by motivation in students and external factors are caused by the environment, infrastructure and weather.